Modelling of macrosegregation in direct chill casting considering columnar-to-equiaxed transition using 3-phase Eulerian approach - Hao, J.; Lin, Y.J.; Nie, Y.; Wu, M.; Ludwig, A. (IOP Publishing, 2015)
A 3-phase Eulerian approach is used to model the macrosegregation during solidification in direct chill (DC) casting of binary bronze (Cu-Sn). The three phases are the melt, the solidifying columnar dendrites and the equiaxed grains. The thermodynamic information of Cu-Sn is included based on published thermodynamic data, which are coupled with the 3-phase solidification model. The occurrence of columnar-to-equiaxed transition (CET), phase interactions, feeding flow, equiaxed sedimentation and their influence on macrosegregation are considered in the model. The model is applied to a laboratory DC casting process of bronze as a benchmark to demonstrate the model potentials. The simulation results of mixed columnar and equiaxed solidification as well as the formation of macrosegregation are presented. The focus of this work is to analyze and discuss the macrosegregation mechanisms by different flow including feeding flow and crystal sedimentation.